2005
DOI: 10.1142/s0218810405002607
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Follow-Up of Silicone-Rubber Interposition Arthroplasty for Osteoarthritis of the Thumb Carpometacarpal Joint

Abstract: There are several surgical options for osteoarthritis (OA) of the thumb carpometacarpal (CMC) joint. This paper presents our long-term clinical and radiographic review of 12 thumbs in ten patients treated by partial trapezial excision and silicone-rubber interposition arthroplasty. The follow-up period averaged 15; three years with a ten-year minimum. Although the procedure provided early pain relief in most thumbs, all but two had mild to severe pain at follow-up. The average range of post-operative palmar ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 17 publications
0
30
0
3
Order By: Relevance
“…Trapezial resection with ligament reconstruction and tendon interposition (LRTI) is the most popular of the available surgical alternatives while others favor surgery without ligament reconstruction or the less complicated trapezial resection alone [5,14] but patients may experience thumb subsidence and other resultant symptoms and therefore, trapezial retention arthroplasty may be preferable [1,9,20,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trapezial resection with ligament reconstruction and tendon interposition (LRTI) is the most popular of the available surgical alternatives while others favor surgery without ligament reconstruction or the less complicated trapezial resection alone [5,14] but patients may experience thumb subsidence and other resultant symptoms and therefore, trapezial retention arthroplasty may be preferable [1,9,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Devices made from silicone, Gore-Tex, Marlex, and other synthetic materials have previously been linked to pain, redness, chronic inflammation, and erosive/remodeling changes in bone [20]. Compressive loads and shear forces in the thumb base may have caused these implants to wear, resulting in reactive changes to microscopic particles of silicone or other materials being attacked by the body's immunological system.…”
Section: X-ray Evaluationmentioning
confidence: 99%
“…24 A joint capsule by itself cannot offer enough stability to the implant because it will not attach to the implant, and frequently the poor quality of capsular tissue after trapeziectomy precludes adequate encapsulation of the implant. 18 In an effort to improve stability, authors have suggested various techniques of capsular reinforcement with the use of different tendon slips.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials using silicone arthroplasty for TMC arthritis, surgeons did not use prosthesis anchoring techniques. 10,20,24 Van Cappelle et al 18 used an FCR sling for ligament reconstruction and temporary Kirschner wire fixation between the thumb and index metacarpals in only 6 of their 35 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical methods are available to reconstruct this joint (complete trapeziectomy with or without tendon interposition, 1-3 arthrodesis, 4 and silicone implants 5,6 ). All of these methods have their own advantages and disadvantages.…”
mentioning
confidence: 99%